Competencia de robots insectos como estrategia didáctica innovadora en la Educación Básica - Piñaloza Morales, Gabriela Judith (2025)
The present research implements an insect robot competition as an innovative didactic strategy in basic education. The study is focused on the design, construction, and evaluation of four insect-like robots, using recyclable materials and some basic electronic components, to promote more dynamic learning and the understanding of technical concepts, thus developing skills such as creativity, teamwork, and problem-solving. The methodology is based on the design-based research model that includes four main phases: Analysis and Exploration, Design and Construction, Evaluation and Reflection, and Implementation and Documentation. Functional tests were carried out after constructing the insect robots, and a competition was executed in which 31 students of the Simón Rodríguez institution participated. Throughout the insect-inspired robotics challenge, the students strengthened their technical skills, perfected design strategies, and showed greater enthusiasm, reflecting a clear evolution in their ability to face competitive challenges.